Effect of Adenosine on Myocardial Protection as an Adjunct to Cardioplegia during Coronary Artery Bypass Surgery (University Heart Journal, 2018)
Background: Adenosine (ADO) has been known to have beneficial effects against tissue injury after myocardial ischemia. So, this study was carried out to investigate the cardio protective effect of exogenous ADO pretreatment as an adjunct to cold blood cardioplegia during coronary artery bypass surgery.Materials and methods: 50 patients (25 in each group) with coronary artery disease undergoing CABG were randomly assigned to both groups: Group A received regular institutional high-potassium ([K+] 20 mol/ 1) cold (12 °C) blood cardioplegia and Group B received 250 ug/ kg adenosine pretreatment followed by antegrade high-potassium cold (12 °C) blood cardioplegia after clamp-on. Clinical outcomes were observed before, during and after the operation.Results: There was no difference regarding operative parameters in two groups. Time to arrest was significantly shorter in group B compared to Group A, indicating that adenosine has the potential to enhance the efficacy of cardioplegic arrest. Plasma level markers of myocardial damage: cardiac Troponin I (cTnl) obtained from serial venous blood samples were significantly lower in group B during cTnl at 10 min after declamping of cross clamp and 12 hours post-operative period than group A. There was significantly decreased requirement of inotrope in group B during 1st 24 hrs. Other postoperative outcomes (mechanical ventilation, ICU stay, postoperative arrhythmia and in hospital mortality were similar in both groups.Conclusion: Decreased level of cardiac enzymes and lower inotropic requirement suggests that a optimal myocardial protection with less cellular damage is obtained with adenosine pretreatment as adjunct to cold blood cardioplegia.University Heart Journal Vol. 14, No. 1, Jan 2018; 21-23